2013
DOI: 10.1016/j.bjane.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laryngeal mask airway supreme and laryngeal mask airway proseal for laryngopharyngeal trauma and postoperative morbidity in children

Abstract: LMA supreme insertion is faster and easier than LMA proseal and causes less laryngopharyngeal injury than LMA proseal in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In addition, another study comparing the laryngeal mask airway Supreme with the laryngeal mask airway ProSeal did not show any differences in airway leak pressures, or the overall clinical performance of either device (61). Some studies have also demonstrated that the laryngeal mask airway Supreme is faster to insert than the laryngeal mask airway ProSeal (60,62). The laryngeal mask airway Supreme has also performed well as a resuscitation device in neonates.…”
Section: Laryngeal Mask Airway Supremementioning
confidence: 99%
“…In addition, another study comparing the laryngeal mask airway Supreme with the laryngeal mask airway ProSeal did not show any differences in airway leak pressures, or the overall clinical performance of either device (61). Some studies have also demonstrated that the laryngeal mask airway Supreme is faster to insert than the laryngeal mask airway ProSeal (60,62). The laryngeal mask airway Supreme has also performed well as a resuscitation device in neonates.…”
Section: Laryngeal Mask Airway Supremementioning
confidence: 99%
“…To prevent air leaks in many supraglottic airway devices like classic LMA and cobraPLA, the cuff pressure should be around 60 cmH 2 O (29, 30). In a study using silicon microchips on the supraglottic airway devices where they touch the oropharyngeal wall, Brimacombe et al showed that when mucosal perfusion pressure is higher than 34 cmH 2 O there is a reduction in capillary blood fl ow (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In a study using silicon microchips on the supraglottic airway devices where they touch the oropharyngeal wall, Brimacombe et al showed that when mucosal perfusion pressure is higher than 34 cmH 2 O there is a reduction in capillary blood fl ow (30,31). Tissue damage occurs with a reduction in capillary blood fl ow (2). Here the tissue damage and throat pain appearing with hemodynamic response may be explained by the cuff pressure and capillary perfusion pressure in the pharyngeal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Compared with the LMA ProSeal, the LMA Supreme was found to be easier to insert and was associated with less pharyngeal injury in children. 10 In a neonatal manikin study, the LMA Supreme was found to outperform the LMA Classic and LMA ProSeal. 11 Compared with a newer second-generation device, the i-gel, the LMA Supreme was associated with higher first attempt success rates and faster times for successful insertion and had similar effectiveness in providing positive pressure ventilation.…”
Section: Basic Sga Insertion Techniquesmentioning
confidence: 99%